Framework para programação off-line de robôs - Bottazzi, Vitor Santos (2007)
This master thesis addresses the on-line programming problems which deals with reduce time integration to manufacture cells thought off-line robots pro¬gramming using exchange file projects. The industrial robot programming is a work for specialist in robotics. Today, this work is very hard because there are many robot manufacturers with different languages and different programming environments. Although, off-line programming is an way that can reduce drastically the machines step time to maintenance. ln this work is proposed a off-line programming environment, capable of extract the boun¬dary information of a piece from neutral files. Handle this information to program some specific application like a piece placement, welding, or pain¬ting of a single piece placed at a stable position. This tool is based in an abstract model to program robots, encapsulate in java classes. The main ad¬vantage of object oriented paradigm is best source code utilization. Grouping the business classes in modules by functionalities, we can reduce complexity between low matching. Recognized patterns like Façade and Template Method constructs the base to develop this programming framework. The programming robot languages used in this work was Rapid, KareI and Melfa Basic IV, respectively languages used by ABB, Fanuc and Mitsubishi cons¬tructors. First experiments demonstrate the feasibility and the efficiency of the approach.